Patient-Reported Global Health Predicts Adverse Health Outcomes in a Cohort Of Patients with Advanced Sarcoma - Husain, Marium; Phillips, Audra; Xu, Menglin; Chen, James L; Tinoco, Gabriel; Liebner, David (International Journal of Human and Health Sciences (IJHHS), 2024)
Objectives: Given the rare nature of sarcoma and the sometimes severe treatment-related effects of chemotherapy, many patients with sarcoma face quality of life (QoL) issues during treatment. Unplanned hospital admission and emergency department (ED) visits can occur from uncontrolled symptoms and ultimately delay treatment regimens, negatively impacting QoL. The PROMIS Global Health (PROMIS-10) surveys are validated tools to assess patients’ physical and mental well-being. We sought to evaluate the correlation between PROMIS-10 scores with unplanned admissions ED visits and patient mortality. Methods: We collected the raw and normalized t-scores for PROMIS-10 surveys for all patients consented to The Ohio State University Sarcoma Registry from 6/1/2018 to 11/20/2019. We collected data on unplanned hospital admissions, ED visits and mortality data. Results: A total of 864 surveys for 112 patients were collected. Mean global physical t-scores (43.7± 8.5) and mental t-scores (47.9 ± 9.2) were lower than reference scores for the general US population (p<0.001). 109 of 112 patients experienced an unplanned admission or ED visit during the study (total of 270 encounters). Physical PROMIS-10 scores were lower for patients experiencing an unplanned admission or ED visit within 30 days of taking the survey (physical: 41.9 vs 44.1, p = 0.006; mental: 46.4 vs 48.2, p = 0.035). Surveys completed prior to death were consistent with a greater level of physical and mental distress (median physicalt-score = 34.9 (range: 23.5 – 50.8) and mental t-score = 43.5 (range: 33.8 – 67.6)). Conclusions: We demonstrated effective evaluation of patients’ physical and mental well-being through survey data during cancer treatment. We are currently performing an updated analysis of the predictive value of the PROMIS-10 survey for adverse events and for treatment-related complications. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S36